Relationship between difficulites in emotion regulation, subjective well being and working alliance between counsellors and client among substance abuseru - Chan, Grace Chee Yan; Ismail, Asmah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
A correlational study was conducted in order to examine the relationship between difficulties in emotion regulation, subjective well-being and working alliance between counsellor and client among substance abusers from ten local residential substance-use treatment centres in Malaysia. A total of 211 participants were recruited through random sampling. The age of participants ranged from 18 to 61 years old (min age 36 years old). Data was collected through the administration of Emotion Regulation Questionnaire, Difficulty in Emotion Regulation Scale, Satisfaction with Life Scale, Loneliness Scale and Counsellor-Patient Relationship Scale. The research intends to explore the associations between aspects of emotion dysregulations with level of satisfaction with life and working alliance between counsellor and client. Data was analysed using Pearson’s correlation. Significant findings revealed that: (a) More difficulties in two aspects of emotion dysregulation are associated with lower satisfaction with life, (b) General difficulties in regulating emotions are linked to higher levels of loneliness, and (c) The relationship between subscales of DERS and working alliance between counsellor and client revealed no significant effect. Nonetheless, counsellors can provide effective service to substance abusers by increasing their subjective well-being through training or modeling of adaptive emotion regulation strategies at the treatment centres.